Three ways VMware made diversity gains stick VMware's 10-year DEI journey offers lessons on prioritizing efforts in ways that sustain long-term success - Boyle, Amber; Green, Tiffany Galvin (MIT Sloan Management Review, 2024)
During VMware's 10-year DEI effort, leaders had to learn about making diversity gains last. VMware successfully increased the percentage of women employees globally and underrepresented employees in the U.S., at rates that stand out in the tech industry. Its journey has lessons on how to prioritize diversity, equity, and inclusion efforts that move the needle in sustainable ways for the long term. Learn from VMware's three best practices for culture change, including an expansive reverse-mentoring program.
Reprint #65312
Keywords: VMware; Diversity in the workplace; Virtual computer systems; Cloud computing; Multiculturalisme en milieu de travail; Systèmes virtuels (Informatique); Infonuagique